2019
DOI: 10.4067/s0718-221x2019005000103
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of some surface properties and thermogravimetric analysis of veneer sheets treated with fire retardants

Abstract: This study investigated the effects of different fire retardant chemicals on surface and thermal properties of veneer sheets. Beech (Fagus orientalis), alder (Alnus glutinosa), poplar (Populus deltoides) and scots pine (Pinus sylvestris) were chosen as wood species and zinc borate, borax, monoammonium phosphate and ammonium sulfate were chosen as fire retardant chemicals. The samples were impregnated by using the immersion method. Some surface properties such as colour measurements and surface roughness of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…45 Many studies have reported that using the family of ammonium phosphate as an activator or fire-retardant material leads to a decrease in the thermal decomposition of the blended polymer. 46,47 The loaded samples exhibited decomposition peaks from about 400-600 °C resulting from the degradation of the remaining backbone chains of the polymers.…”
Section: Thermogravimetric Analysismentioning
confidence: 99%
“…45 Many studies have reported that using the family of ammonium phosphate as an activator or fire-retardant material leads to a decrease in the thermal decomposition of the blended polymer. 46,47 The loaded samples exhibited decomposition peaks from about 400-600 °C resulting from the degradation of the remaining backbone chains of the polymers.…”
Section: Thermogravimetric Analysismentioning
confidence: 99%
“…The parameters used to characterise the wood surface properties are surface roughness and surface free energy (SFE) (Qin et al, 2014). Surface roughness is an important factor in determining surface quality, especially wettability (Akgul et al, 2012;Ayrilmis et al, 2009;Candan et al, 2010Candan et al, , 2012Candan et al, , 2021aCandan et al, , 2021bDarmawan et al, 2017;Dundar et al, 2008;Dundar et al, 2014;Unsal et al, 2010Unsal et al, , 2011Demir and Aydin, 2019). Parameters to determine the interaction between the wood surface and the coating material (wettability) can also be analysed by observing the thermodynamic wetting parameters, such as the SFE (Wålinder, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Wood and wood composites represent a main part of the fuel in many building fires [1]. The ability of materials to ignite when heated at elevated temperatures depends on many factors, such as the thermal properties [2][3][4], the chemical composition of materials [5][6][7], the ignition temperature [8][9][10], the heat flux, and the environment [1,11]. Under fire exposure, wood is degraded with heat transfer and weight loss [12,13].…”
Section: Introductionmentioning
confidence: 99%